Recycling Rare‐Earth Slag for Enhanced Photoelectro‐ chemical Efficiency of a Reduced Graphene Oxide‐Covered CdSe@ZnO Hetero‐Nanostructured Photoanode. Issue 11 (24th August 2016) - She, Xuefeng; Zhang, Zhuo; Baek, Minki; Choi, Mingi; Yong, Kijung; Wang, Jingsong; Xue, Qingguo
Abstract: Breakthroughs in efficient recycling of industrial slag and renewable energy have become subjects of global interest. In this study, rare‐earth oxide (REO) slag is used for the first time in dramatically enhanced photoelectrochemical hydrogen generation by modifying the surface of a photoanode, which is constructed from reduced graphene oxide (RGO)‐covered CdSe@ZnO two‐story hetero‐nanostructures. REO slag is extracted from REO iron ore by mimicking of the ironmaking process, and whole hetero‐nanostructures prepared for photoelectrochemical anode are synthesized by the hydrothermal method. These studies demonstrate that the REO slag significantly promotes the growth of CdSe nanoparticles and can also be used as the OH − source to block hydrolysis of Na2 S and Na2 SO3 in the electrolyte. Moreover, light absorption is fully facilitated by the two‐story structure, and the photoconversion is enhanced via type II cascade band alignment of CdSe and ZnO. In addition, the concentration of holes and efficient charge transfer by RGO can suppress electron–hole recombination and improve the electron lifetime. This study presents a novel REO‐slag‐modified photoanode for high efficiency photoelectrochemical devices and offers the possibility of recycling industrial waste for renewable energy generation. Abstract : Top of the heap : A two‐layer hetero‐nanostructure constructed from ZnO and CdSe nanoparticles as well as reduced graphene oxide, and covered with rare‐earth oxides from slag, is demonstrated as an efficient anode for photoelectrochemical hydrogen generation. The products and fabrication methods used might also have applications in various nanotechnologies and facilitate the efficient use of slag byproducts from ironmaking.